PATHOMORPHOLOGICAL CHANGES OF THE LUNGS OF MATURE MALE RATS IN CONDITIONS OF EXPERIMENTAL OBESITY AND TOBACCO SMOKING - Kuzyk, Yu.I.; Mazur, O.Yu. (World of Medicine and Biology, 2023)
The influence of obesity (with and without passive smoking) on the formation of pathomorphological changes in the lungs was studied in 4 groups of sexually mature male rats: the control group (CL), the group with isolated alimentary obesity (O), the group exposed to isolated exposure to tobacco smoke (S), the group with combined dietary obesity and exposure to tobacco smoke (OS) after 4 months of the experiment. The morphological changes found in the CL group were insignificant. In group S, the presence of changes characteristic of chronic bronchitis and focal emphysema was established. Pathomorphological changes typical for the chronic obstructive pulmonary disease were found in group O: chronic bronchitis, initial manifestations of bronchiectasis formation, pulmonary emphysema, focal pneumosclerosis, and initial manifestations of pulmonary hypertension. In the OS group, the changes were not qualitatively different from those in the O group. It was found that the changes characteristic of chronic obstructive pulmonary disease developed in rats with simulated obesity, regardless of whether the smoking model was used.